Theoretical aspects of supersymmetry - Lim, Zhi Yuan (Nanyang Technological University, 2020)
The Standard Model is currently the most accurate description of our universe. However, in its current form, it is still unable to explain many phenomena and is far from being a complete theory of fundamental interactions. Many ideas have emerged in an attempt to extend the Standard Model and Supersymmetry is arguably the most elegant. In this thesis, we will go through some theoretical elements of Quantum Field Theory and the Standard Model, leading up to a discussion on Supersymmetry. Supergravity is then discussed very briefly as a conclusion.